2019
DOI: 10.1039/c9lc00115h
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of multiple NT-proBNP clinical samples utilizing an aptamer-based sandwich assay on an integrated microfluidic system

Abstract: An integrated microfluidic platform was developed for the simultaneous detection of NT-proBNP, a widely studied biomarker for heart failure diagnosis, in up to six clinical samples within 25 min by using a novel aptamer-based sandwich assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Related reports indicate that hypoxia-ischemia, microcirculatory disorders, oxidative stress, and stimulation of pro-inflammatory factors lead to increased cardiac secretion of NT-proBNP (10). The only mode of removal of NT-proBNP is glomerular filtration, the level of which is mainly affected by renal function (11), and is not affected by the natriuretic peptide receptor. Some studies also found that elevated serum NT-proBNP in hyponatremia is caused by craniocerebral diseases, such as infection and bleeding (12).…”
Section: Discussionmentioning
confidence: 99%
“…Related reports indicate that hypoxia-ischemia, microcirculatory disorders, oxidative stress, and stimulation of pro-inflammatory factors lead to increased cardiac secretion of NT-proBNP (10). The only mode of removal of NT-proBNP is glomerular filtration, the level of which is mainly affected by renal function (11), and is not affected by the natriuretic peptide receptor. Some studies also found that elevated serum NT-proBNP in hyponatremia is caused by craniocerebral diseases, such as infection and bleeding (12).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic illnesses, the monitoring of certain biomarkers over time can be reflective of the patient’s recovery or treatment. For many integrated microfluidic devices, tests have been reported to be complete within one hour, with some devices completing the test in only 10 min [ 63 , 64 , 65 , 66 ]. The shorter turnaround time can be combined with shorter detection times to maximize the speed at which results can be obtained from these tests.…”
Section: Integrated Microfluidic-based Platforms (Imps)mentioning
confidence: 99%
“…Monitoring the circulatory levels of a relatively new biomarker, N-terminal prohormone of B-type natriuretic peptide (NT-proBNP), is a meaningful way for the early risk evaluation of HF. Sinha et al [19] developed an ingeniously designed, pneumatically-driven, automatic integrated microfluidic platform equipped with micropumps, micromixers, and microvalves for the simultaneous detection of NT-proBNP (Fig. 5.3).…”
Section: Biomarker Detectionmentioning
confidence: 99%
“…This method may serve as a promising tool for early diagnosis of HF, and the integrated microfluidic chip can be extended for the detection of other Ref. [19] by permission of the Royal Society of Chemistry biomarkers as well when adopting other aptamers. Therefore, it can potentially serve as a promising device providing widespread clinical applications.…”
Section: Biomarker Detectionmentioning
confidence: 99%